Enhancing reading comprehension: A review of traditional and online active learning pedagogies - Abu Baha, Osama; Mat Daud, Nuraihan (International Journal of English and Education, 2013)
There are extensive variety of reading comprehension strategies proposed by reading programmes and researches (McLaughlin and Allen 2002; Vacca, 2002; Duke and Pearson 2002). The National Reading Panel (2000) and Cameron (2009) identified helpful results for some strategies, particularly activating prior knowledge (previewing), summarizing, asking and answering questions, evaluating, visualizing, vocabulary knowledge and making predictions. The Panel also highlighted that a combination of strategies can be effective if taught within an active and cooperative environment. Since this article proposes a link between the adoption of an M- active (Mobile and active) learning pedagogy and enhancing reading comprehension strategies, the review will focus on four major topics which are reading comprehension strategies, active learning pedagogy, mobile learning and virtual classes.